THE ROAD TO FISCAL DECENTRALISATION OF MUNICIPALITIES IN REPUBLIC OF BULGARIA - Vanya PANTELEEVA (Challenges of the Knowledge Society)
This publication is dedicated specifically to local taxes, given their importance for the actual achievement of local self-government in the Republic of Bulgaria. Here, financial decentralisation is understood as a way to strengthen the legal role and economic power of local government. An expression of financial decentralisation de lege lata are the tourist tax and the patent tax.